#TITLE_ALTERNATIVE# - Adhi Utama (NIM 122 03 041), Fia
Abstract: In many oil fields, often to occur some serious problems, one of them is a phenomenon called water coning. Commonly, reservoirs with bottom aquifer have a tendency to experience with this kind of problem. Large drawdown at the oil zone often to cause instability at Water Oil Contact (usually a cone shaping), that moves upward to the perforation set. One conventional method that is used to overcome this problem is completing the upper section of the pay zone to prevent or at least to delay water coning. Not only that, the well should be produced below its critical rate. Due to producing oil rate below its critical rate may proven not economical, an alternative method that has been investigated by many authors is Downhole Water Sink (DWS). The primary mechanism of this technology is to provide an adversary to pressure drawdown by producing water through the water zone perforation. By doing it, the pressure drawdown created in the water zone would allow a higher production in the oil zone. The success rate of Downhole Water Sink completion depends on the producing rate ratio between oil zone and water zone perforation set. And there should be only oil flow at the top completion and only water flow in the bottom completion (segregated flow). This paper analytically examines the critical flow rate that will provide the segregated flow under Downhole Water Sink completion and in anisotropic reservoir. The results are compared with a numerical simulation by plotting the calculation results in an Inflow Performance Window (IPW) from preceding simulation and also comparing to the field data.